Restricted liability in the face of the prohibition of the suspension of the sentence in the crime of aggression against women - Vega Toro, Edgar Ronulfo (2023)
The purpose of this article is to analyze the implication of restricted liability –age group– against the prohibition of the suspension of the execution of the sentence in the crime 122B sanctioned with short sentences, where both legal institutions share a quasi legal situation. Due to restricted liability, its application was restricted to certain crimes, despite this, the restriction has been declared unconstitutional through diffuse constitutional control. It will be analyzed if the prohibition of suspension of the execution of the sentence in the crime 122B can be inapplicable in attention to the similar situation of the age group that represents the restricted responsibility.